Vacuolar sequestration as a coping mechanism in cadmium-treated water hyacinth [Eichhornia crassipev (Mart.) Solms.] - Puzon, Juliana Janet M. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2008)
Eichhornia crassipes (Mart.) Solms. plants were grown in nutrient solutions with 0.05, 0.5 and 5.0 mg L-1 CdCI2for 1,3 and 7 d. Growth responses of roots, stems, petioles and laminae were evaluated. The biomass and chlorophyll content of the laminae were significantly affected by age of the leaf and cadmium treatment levels, while the leaf surface area was significantly affected by cadmium treatments only. The chlorophyll content of young laminae increased on the 1st and 7th d of CdCI 2 exposure. Atomic absorption spectrophotometric (AAS) analyses revealed that significantly high levels of Cd were taken up by various vegetative organs of E. crassipes. Based on linear regression analysis, Cd levels increased with an increase in concentration, as well as prolonged Cd exposure. Generally, mature vegetative organs took up greater amounts of cadmium compared with the younger organs. The analyses of Cd content and S content through inductively coupled plasma - atomic emission (ICP-AES) spectrometry revealed the localization of Cd in all subcellular components of the cells from young and mature laminae of Cd-exposed E. crassipes plants and the ultimate sequestration of Cd ions in the vacuoles. The presence of S in the vacuoles indicated its role, as well as those of other S- containing compounds, in the chelation and sequestration of Cd into the vacuoles. This is the first report on vacuolar sequestration of cadmium as a tolerance mechanism in E. crassipes, lending support to numerous reports on the efficacy of E. crassipes as a cadmium phytoremediator.